2016
DOI: 10.5901/mjss.2016.v7n4s2p139
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Governance Mechanisms on Social Responsibility Disclosure

Abstract: The aim of this study was to investigate the relationship between some of the corporate governance mechanisms on social responsibility disclosure. To measure the level of corporate social responsibility information disclosure, according to the research of Nirwanto et al. (2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a quantitative change, the point at issue is economic growth; a qualitative change implies a structural change, a change in the content of development, or the acquisition by the economic system of new characteristics. Social characteristics of development are often considered in addition to economic parameters, which make it possible to fully assess the degree of development of any economic subject and region [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a quantitative change, the point at issue is economic growth; a qualitative change implies a structural change, a change in the content of development, or the acquisition by the economic system of new characteristics. Social characteristics of development are often considered in addition to economic parameters, which make it possible to fully assess the degree of development of any economic subject and region [4].…”
Section: Introductionmentioning
confidence: 99%
“…found that the proportion of independent directors of ShCC in Malaysia had no significant relationship with the quality of voluntary disclosure.Board size also consider important item in the board matters as Siregar & Bachtiar (2010) found that a larger board size able to monitor the action of top management and Chief Executive Officer (CEO) from any action that will harm shareholder's interest. A number of studies had found that board size positively influence the extent of voluntary disclosure, CSR disclosure or sustainability disclosure(Ahmed Haji & Mohd Ghazali, 2013;Mahmood et al, 2018;Mohd Ghazali, 2010;Zolfaghar Arani, 2016). However, there were some studies that found larger board size will decrease the ability to control and leads to a lower voluntary and environmental disclosure(Cheng & Courtenay, 2006; Ezhilarasi & Kabra, 2017; Halme & Huse, 1997; Vafeas, 1999; Wan Abdullah et al, 2012).…”
mentioning
confidence: 99%